The homeostasis-maintaining metabolites from bacterial stress response to bacteriophage infection suppress tumor metastasis. Issue 43 (25th October 2018) - He, Tianliang; Jin, Min; Xu, Chenxi; Ma, Zhongjun; Wu, Fufang; Zhang, Xiaobo
Abstract The antiviral metabolites from bacterial stress response to bacteriophage infection can maintain homeostasis of host cells, while metabolism disorder is a remarkable characteristic of tumorigenesis. In the aspect of metabolic homeostasis, therefore, the antiviral homeostasis-maintaining metabolites of bacteria may possess anti-tumor activity. However, this issue has not been addressed. Here we show that the homeostasis-challenged maintaining metabolites from deep-sea bacteriophage-challenged thermophile can suppress tumor metastasis. The results indicated that the metabolic profiles of the bacteriophage GVE2-infected and virus-free thermophileGeobacillus sp . E263 from a deep-sea hydrothermal vent were remarkably different. Thirteen metabolites were significantly elevated and two metabolites were downregulated in thermophile stress response to GVE2 infection. As an example, the upregulated L-norleucine was characterized. The data showed that L-norleucine had antiviral activity in thermophile. Furthermore, the in vitro and in vivo assays revealed that L-norleucine, as well as its derivative, significantly suppressed metastasis of gastric and breast cancer cells. L-norleucine interacted with hnRNPA2/B1 protein to inhibit the expressions of Twist1 and Snail, two inhibitors of E-cadherin, and promote the E-cadherin expression, leading to the inhibition of tumor metastasis. Therefore, our study presented that antiviral homeostasis-maintaining metabolites of microbes might be a promising source for anti-tumor drugs.